Dampak Invasi Rusia Ke Ukraina Terhadap Reaksi Pasar Modal Pada Perusahaan Minyak dan Gas Bumi, Makanan dan Minuman Yang Terdaftar di Bursa Efek Indonesia - Aulia, Nadia; Fikri, M. Ali (Fakultas Ekonomi dan Bisnis Unram, 2024)
This research aims to test whether there is an impact of the Russian invasion of Ukraine on oil and gas, food and beverage companies. The variables used in the research are abnormal returns and trading volume activity. This research was conducted on Oil and Gas, Food and Beverage companies listed on the Indonesia Stock Exchange, the sample for this research was 60 companies. This research was conducted on the Indonesia Stock Exchange (BEI) in 2022 using qualitative research methods with an event studyapproach. study). The results of this research show that there is a difference betweenAbnormal Returns while in the second there is no difference in Trading Volume Activity.